Wykorzstanie dynamicznych modeli panelowych PKB do oceny regionalnego rozwoju Unii Europejskiej - Bal-Domańska, Beata (The Application of Dynamic Panel Models for the Description of European Regional Space Developmen, 2007)
The article presents an econometric analysis of Gross Domestic Product per capita depending on the level and structure of labour force in the European Union regional space. The panel on European Union NUTS 2 regions in the period of 1999-2002 was used for model estimation. This facilitated taking into consideration the specific nature of particular regions, economies as well as the changeability of factors in time in the model. The carried out analysis points to an observation that the structure of labour force plays an important role in constructing developmental processes at regional level with main emphasis on the number of service sector employees.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 79-88